Cultural Ecosystem Services of Rattan Garden: The Hidden Values - Afentina, Afentina; McShane, Paul; Plahe, Jagjit; Wright, Wendy (European Journal of Sustainable Development, 2017)
Ecosystem Services (ES) are services provided to local communities by natural resources. Cultural Ecosystem Services (CES) are the nonmaterial benefits that people obtain from ecosystems. ES, and particularly CES are often omitted from cost-benefit analyses associated with development plans in favour of a focus on maximizing economic benefits. Consequently, economic development can lead to the disappearance of cultural values such as local knowledge, and cultural identity. This research attempts to understand and analyze CES and benefits provided by rattan gardens for local communities in Tumbang Runen village in Indonesia. Information about CES was obtained through in-depth interviews with key informants, focus group discussions with farmers, and observations of daily activities of local people. This research revealed that residents of Tumbang Runen village attach strong cultural importance to their rattan gardens, including spiritual, heritage and local knowledge values. The spiritual aspects of CES include the use of some plant species in rituals and healing ceremonies. Local people consider rattan to be historically important, intimately linking people with their ancestors and their belief system. Rattan gardens and rattan cultivation also serve as cultural symbols, facilitating the maintenance of practices, beliefs, and knowledge across generations. The importance of rattan gardens to the local community should be communicated to policy makers and included in sustainable development strategies Keywords: Cultural ecosystem services, rattan garden, local community, sustainable development